IMPLEMENTASI KURIKULUM 2013 DALAM PEMBENTUKAN KARAKTER SISWA - aini, shofia isnaini (Jurnal Pena Ilmiah, 2019)
The application of the 2013 curriculum focuses on three aspects of assessment, namely affective, cognitive, and psychomotor. As we know in this day and age the character of students has begun to fade. So from that the formation of the 2013 curriculum is expected to shape the character of students. This research is a library research. Therefore, all data is taken from books or papers related to the discussion. From the implementation of the 2013 curriculum which is currently being implemented in Indonesia the character of the students who had previously faded is now starting to form again. This indicates that the goal of implementing the 2013 curriculum has been achieved. This is seen from the results of the assessment of the three aspects in the younger generation (students), namely the affective, cognitive, and psychomotor aspects.